Forecasting the production and export of shrimp in Bangladesh: a policy focused time series analysis - Mobin Hossain Shohan; Mohammad Mahfujul Haque (Frontiers in Aquaculture)
IntroductionThe study analyses shrimp industry of Bangladesh, highlighting its growth potential amid challenges such as declining export volumes, quality compliance issues, and competition from low-cost producers. Despite expanded farming areas and increased production, exports have fallen due to food safety issues, weak infrastructure, and inadequate regulatory compliance.MethodsThe study employs the Vector Autoregression (VAR) model to forecast shrimp production and exports, analyzing 33 years of data (1991–2023) to identify bottlenecks and policy gaps. Using statistical tests, co-integration analysis, and a literature review, it highlights challenges in legislative policies and quality compliance, offering strategies to enhance standards and global competitiveness.Results and discussionThe analysis reveals a steady rise in shrimp production, contrasting with a two-fold decline in export quantities from 2011 to 2023, largely due to quality non-compliance and contamination. The VAR(1) model predicts a slight decline in production by 2026–27, with exports potentially decreasing by a factor of 3.2 compared to 2010–11. Key challenges include hazardous residues, poor management practices, and disease outbreaks. Legislative analysis highlights policy gaps, weak enforcement, and insufficient infrastructure as significant barriers to meeting international standards. Addressing these challenges is critical for enhancing the global competitiveness of the industry. Recommendations include incentivizing organic farming under certification, improving post-harvest infrastructure, adopting advanced disease management technologies, and establishing regional testing facilities. A unified shrimp marketing policy is essential to enhance quality, sustainability, and competitiveness in global markets. These strategies aim to align the industry with international standards, boost exports, and ensure long-term sustainability.